Splintering urbanism networked infrastructures, technological mobilities and the urban condition - Graham, Stephen 1965-; Marvin, Simon 1963- (Routledge, 2001)
This text offers an international and interdisciplinary analysis of the complex interactions between infrastructure networks and urban spaces. Drawing on case studies and examples from across the globe, it offers a statement on the urban condition.
Keywords: Informatienetwerken; Informatietechnologie; Infrastructuur; Metropolen; Mondialisation; Réseaux (Aménagement du territoire); Sociale aspecten; Société informatisée; Société postindustrielle; Urbanisme; Villes, Effets des innovations sur les; Gesellschaft; Globalisierung; Stadt; Cities and towns; Globalization; Information society; Infrastructure (Economics) -- Computer networks; Technology -- Social aspects; Netzwerk; Informationsgesellschaft; Stadtentwicklung; Infrastruktur; Rechnernetz; Prognose